FORMATION OF SOCIAL ACTIVITY AMONG STUDENTS: A MULTIFACETED APPROACH - Gulyamrva Nadira Gafurovna (International Scientific and Current Research Conferences, 2023)
Social activity among students is a critical aspect of their personal and academic development. This article explores the multifaceted nature of social activity formation among students, drawing on research from various fields to understand its importance, factors influencing it, and strategies for fostering positive social engagement in educational settings.